Antiadenovirus Activities of Several Classes of Nucleoside and Nucleotide Analogues - Naesens, L. (American Society for Microbiology, 2005)
The absence of any formally licensed antiadenovirus drugs and the increasing incidence of life-threatening adenovirus infections in immunosuppressed patients warrant the development of effective antiadenovirus compounds. A detailed study was performed on the antiadenovirus activities of several classes of nucleoside and nucleotide analogues in human embryonic lung fibroblast cells. The antiadenovirus activities were evaluated by three methods, viz., evaluating the adenoviral cytopathic effect, monitoring cell viability by a colorimetric assay, and real-time PCR quantitation of viral DNA as a direct parameter for virus replication. The most active and selective compounds were the acyclic nucleoside phosphonate analogues cidofovir, its adenine analogue (S)-9-(3-hydroxy-2-phosphonylmethoxypropyl)adenine [(S)-HPMPA], and the new derivative (S)-2,4-diamino-6-[3-hydroxy-2-(phosphonomethoxy)propoxy]pyrimidine [(S)-HPMPO-DAPy]; the N7-substituted acyclic derivative 2-amino-7-(1,3-dihydroxy-2-propoxymethyl)purine (S-2242); and the 2′,3′-dideoxynucleoside analogues zalcitabine and alovudine. No antiadenovirus activity was observed for the antiviral drugs ribavirin, foscarnet, acyclovir, penciclovir, and brivudin, while ganciclovir displayed modest activity. However, in human osteosarcoma cells transfected with herpes simplex virus thymidine kinase, ganciclovir demonstrated highly potent antiadenovirus activity, suggesting that the efficacy of ganciclovir against adenovirus is limited by inefficient phosphorylation in adenovirus-infected cells, rather than by insufficient inhibition at the viral DNA polymerase level. Collectively, our antiviral data show that the adenovirus DNA polymerase exhibits sensitivity to a relatively broad spectrum of inhibitors and should be studied further as an antiviral target in antiadenovirus drug development programs.